'It feels like someone is hammering my feet': Understanding pain and its management from the perspective of people with multiple sclerosis. (April 2015) - Harrison, Anthony M; Bogosian, Angeliki; Silber, Eli; McCracken, Lance M; Moss-Morris, Rona
Background: Pain affects around 63% of people with multiple sclerosis (pwMS). Biomedical treatments demonstrate limited efficacy. More research is needed to understand pain from the individual's perspective in order to better inform a patient-centred approach that improves engagement, self-management and outcome. Objective: The objective of this paper is to explore pwMS' experience and responses to pain, and their perspectives on pain management. Methods: Twenty-five in-depth, semi-structured telephone interviews were conducted. Interviews were audiotaped, transcribed and analysed using an inductive thematic analysis approach with elements of grounded theory. Results: Key themes included vivid descriptions of pain and beliefs that pain is unpredictable, a sign of damage and may worsen. Anger was a common emotional response. Two dominant pain management themes emerged: one related to pain reduction and another to acceptance. Those focusing on pain reduction appeared to engage in cycles in which they struggled with symptoms and experienced continued distress. Conclusion: Findings identify pain-related beliefs, emotional reactions and disparate pain-management attitudes. All may influence pwMS' responses to pain and what they ask of their clinicians. Uncovering pwMS' personal beliefs about pain, and introducing a broader biopsychosocial understanding of pain in the clinical context, may provide opportunities to rectify potentially unhelpful management choices and enhance pain acceptance.